Optimization, high-temperature resistance, and sulfate durability of basalt powder-blended alkali-activated slag mortars - Arslan, Furkan; Dener, Murat; Karatas, Mehmet; Benli, Ahmet (Elsevier, 2026)
This study investigates the feasibility of using basalt powder (BP), an industrial by-product with limited reactivity, as a partial substitute for granulated blast furnace slag (GBFS) in alkaliactivated systems. A comprehensive experimental program was conducted in two stages: first, a systematic optimization was performed by varying mixture parameters, including BP content, alkali dosage, activator modulus, and curing temperature to evaluate compressive strength development; second, selected binder compositions were used to produce self-compacting mortars, which were further examined for flexural strength, high-temperature resistance, and sulfate durability. The results demonstrated that moderate substitution levels (up to 20-30 % BP) could achieve satisfactory compressive strength, particularly under elevated curing temperature (60 degrees C) with 8 % Na2O and low to moderate modulus values. At 300 degrees C, mixtures with 20 % BP exhibited strength enhancement due to additional geopolymerization, demonstrating superior thermal stability compared to the control. Crucially, the incorporation of BP enhanced sulfate resistance, with the 40 % BP mixture exhibiting a slight increase in compressive strength after long-term exposure, in contrast to the marked deterioration of the GBFS-only system. Consequently, this study demonstrates that BP can be effectively utilized as a sustainable binder component, offering a practical solution for waste management while enhancing the durability of alkali-activated mortars against aggressive conditions.
Keywords: Alkali-activated materials; GBFS; Natural pozzolan; Curing temperature; Activation parameters; Sulfate resistance